PARATE EKSEKUSI ATAS TANAH HAK MILIK SEBAGAI JAMINAN UTANG - Elvira Diba Fahlevi; Irene Eka Sihombing; Diba Fahlevi, Elvira (Faculty of Law, Universitas Trisakti, 2023)
A credit arrangement existed between M.Nova Irdiansa, the debtor, and Bank CIMB Niaga, the creditor, in the case that took place on October 20, 2014. In its ruling on the issue, the Supreme Court's panel of judges rejected the plaintiffs' request for a memorandum of cassation, which was included in the judgement. The plaintiffs in this case, M.Nova Irdiansa and Hj.Enny Adriati, are subject to Article 6 of the Mortgage Act (Parate Eksecusi), which provides legal certainty for debt repayment. The issue is whether Bank CIMB Niaga's execution of mortgage rights on freehold land through a public auction complies with the Minister of Finance Regulation Number 27/PMK.06/2016. Research method is normative law, analytical descriptive, the source literature studies, interviews informants and using deductive logic method. The results the research, discussion and conclusion are that the judge rejected the plaintiffs' cassation because Bank CIMB Niaga was proven to have been authorized by law to carry out executions without the consent of the debtor granting Mortgage Rights (Parate Execution), the implementation of which was based on the promise in Article 2 number 6 Deed of Granting Mortgage Rights (APHT) Number 233/2014, namely by way of auction because it had been agreed beforehand.